Spectrophotometric Determination of Calcium with Dibromo-p-methylsulfonazo. (13th April 2020) - Li, Xiao-Dong; Zhai, Qing-Zhou
Abstract : Calcium is a necessary trace element in the human body, and its low or high content in the human body is not appropriate. It is very meaningful to study the level of calcium in the human body and to determine calcium content in blood. As people take calcium through food, the determination of calcium content in certain tea and calcium supplements is of great significance. In this study, a new method for the determination of calcium was established using dibromo- p -methylsulfonazo as a chromogenic agent. In this article, the optimal conditions for the color reaction of Ca 2+ with dibromo- p -methylsulfonazo were established. In a hydrochloric acid medium, Ca 2+ and dibromo- p -methylsulfonazo form a blue complex. At 624 nm maximum absorption wavelength, the apparent molar absorptivity for the determination of calcium is 3.32 × 10 4  L·mol −1 ·cm −1 . Beer's law is applied for 0–0.60  μ g/mL. The method has already been used in the determination of calcium in blood serum, whole blood, tea leaf, and calcium fudge with satisfactory results.